Lightweight Security for MQTT-SN - H. Amaran, M.; S. Rohmad, M.; H. Adnan, L.; N. Mohamed, N.; Hashim, H. (International Journal of Engineering and Technology, 2018)
This study discusses a method to secure Message Queuing Telemetry Transport-Sensor network (MQTT-SN). MQTT-SN is a popular data communication protocol used in developing IoT applications and can be secured by augmenting it with a security scheme. In this work, several lightweight encryption schemes to be used in tandem with MQTT-SN were tested and analysed. The best algorithm is identified based on the speed of encryption and overall power consumption when implemented in IoT environment. It was found that L-BLOCK is the overall performer in securing MQTT-SN and should be highly considered when developing IoT applications.
Keywords: MQTT-SN; MQTT; Internet of Things; Lightweight Security; Encryption; LBLOCK; UDP; Block Cipher.